Imaging patterns of muscle atrophy - Weber, Marc-André; Wolf, Marcel; Wattjes, Mike Peter (Seminars in musculoskeletal radiology, 2018)
The role of muscle imaging in the diagnosis of inherited and acquired muscle diseases has gained clinical relevance. In particular, magnetic resonance imaging (MRI) is increasingly being used for diagnostic purposes, especially with its capability of whole-body musculature assessment. The assessment and quantification of muscle involvement in muscle diseases can be of diagnostic value by identifying a certain involvement pattern and thus narrowing the differential diagnosis and supporting the clinical diagnosis. In addition, more recently the role of imaging has gone beyond diagnostic purposes and includes disease as well as treatment monitoring. Conventional and quantitative muscle MRI techniques allow for the detection of subclinical disease progression (e.g., in muscular dystrophies) and is a powerful surrogate outcome measure in clinical trials. We present and discuss recent data on the role of conventional and quantitative MRI in the diagnosis and monitoring of inherited dystrophic muscle diseases as well as muscle denervation.
Gesehen am 28.06.2019